2009
DOI: 10.1143/jjap.48.120217
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Bare Porous Surface on 6H-SiC Substrates by Photo-Electrochemical Etching

Abstract: A new method for obtaining a bare porous surface is proposed. Photo-electrochemical etching for forming a porous layer generally results a skin layer on it. The in-situ observation of the etching process revealed that the skin layer can be peeled off by introducing a dark period at the end of the porous formation process. The dark condition switched over the etching mode to an electro-polishing mode, and generated gas bubbles at the region just below the skin layer. The peeling of the skin layer is the result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Taking into account the above experimental results, we discuss the self-fabrication mechanism of the porous membrane. As reported in former research papers, 13,15,18) we also observed small pores using the SEM on the surface layer along shallow grooves that were created during mechanical mirror polishing. The trigger of pore formation can be current crowding because of its lower resistivity due to a thinner oxide layer.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…Taking into account the above experimental results, we discuss the self-fabrication mechanism of the porous membrane. As reported in former research papers, 13,15,18) we also observed small pores using the SEM on the surface layer along shallow grooves that were created during mechanical mirror polishing. The trigger of pore formation can be current crowding because of its lower resistivity due to a thinner oxide layer.…”
Section: Resultssupporting
confidence: 81%
“…Finally, the UV-irradiation effect on the peeling-off process is discussed. In our former work, 13) peeling-off of the membrane was observed when the UV-irradiation was interrupted. This phenomenon can be explained by a similar mechanism to that in the double-step electrochemical etching process without UV-irradiation.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations